Conference Reports - -, - (CAML Review / Revue de l’ACBM, 2020)
The COVID-19 pandemic caused many conference cancellations, while others moved to the virtual environment. Below are reports from five virtual conferences: New England Chapter of the MLA by Marci Cohen Mountain-Plains Chapter of the MLA: Two Perspectives by Christine Edwards and Ellwood P. Colahan Teaching Music Online in Higher Education by Kevin Madill Association for Recorded Sound Collections by Rebecca Shaw Music Encoding Conference by Emily Hopkins, Yaolong Ju, Juliette Regimbal and Martha Thomae